Comparative LC-MS analysis of bioactive compounds, antioxidants and antibacterial activity from leaf and callus extracts of Saraca asoca - Arumugam Vignesh (Elsevier, 2022)
Abstract:: Background: Saraca asoca (Roxb.) Willd. is a plant belonging to the Detarioideae subfamily of the legume family. It is an important and most ancient tree species of Peninsular India and Sri Lanka. The Ashoka is an ornamental and medicinal plant and this species is classified as ‘vulnerable’ under International Union for Conservation of Nature (IUCN) red list Purpose: The present study was aimed for a comparative study between wild plant and callus extract, concerning analysis of phytochemical constituents, antioxidant and antibacterial activity of S. asoca using different solvents extracts Method: The preliminary phytochemicals contents, antioxidants and antibacterial analysis of in vivo plant and in vitro callus extracts for its phytocompounds analysis using Liquid Chromatography-Mass Spectrometry (LC-MS) techniques Results: The leaf were cultured in Murashige and Skoog's (MS) medium supplemented with 0.3 mg/L 6-Benzylaminopurine (BAP) and 0.6 mg/L 2,4-Dichlorophenoxyacetic acid (2,4-D), achieved better callus initiation within 16 days and 80% callus responses and 42 mg of fresh weight. The phytochemical and pharmaceutical activities were compared with different solvents of in vivo leaf and in vitro callus extracts of S. asoca. Among these, in vitro callus methanol extracts showed the highest amount of phenolics (984.20 ± 23.14 mg GAE/g extract) and flavonoids (655.33 ± 42.51 mg QE/g extract). The 2,2-Diphenyl-1-picrylhydrazy (DPPH) assay also showed better scavenging (IC50 38.79 ± 2.35 mg/mL) and chelating activities (98.79 ± 3.35 mg EDTA E/g extract). The callus methanol extract showed significant antibacterial activity against the Enterococcus faecium (Zone of Inhibition 17 mm) and Salmonella typhi (ZOI 14 mm). The LC-MS analysis of callus methanol extract exhibited eight compounds mainly flavonoids such as quercetin, naringenin and epiafzelechin Conclusion: The results manifested that the callus extracts has better antioxidants and antimicrobial activity compared to the wild plant, hence the conservation could be achieved by the micropropagation techniques, Therefore, the present study revealed the presence of various bioactive compounds in the callus extract of S.asoca indicating that the compounds can be used as therapeutic drugs without destroying the wild plant.